KEHIDUPAN PENYANDANG TUNA RUNGU (Studi Kasus Keluarga “KM” di Banjar Celuk, Kelurahan Panjer, Kecamatan Denpasar Selatan) - Henny Sirait, Aldu; Suriadireja, Purwadi; Sudiarna, I Gusti Putu (Humanis; Volume 17. No. 1. Oktober 2016, 2017)
A deaf person who has a lack or loss of hearing ability due to partial damage hearing instruments that have problems in language development. There is a tendency that a child who has often followed by a deaf mute. This condition seems difficult to avoid because the two into a series of cause and effect. This condition makes it difficult communication with society. They use symbols to convey ideas and feelings with sign language and body language such that a mutual understanding. Thus the deaf requires special treatment to shape good behavior, communicating with the environment and society relations.
Keywords: Deaf, Family, Society